2019
DOI: 10.21776/ub.jpacr.2019.008.02.475
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics, Antioxidant Activity, Total Phenol, and Caffeine Contents in Coffee of Date Seeds (Phoenix dactylifera L.) of Red Sayer Variety

Abstract: Red Sayer is one of the date varieties from the United Arab Emirates. This variety is one type of dates that is imported into Indonesia and used as processed date palm juice producing waste, namely date seeds. Date seeds can be made into some coffee that is rich in antioxidants and does not contain caffeine. The purpose of this study is to determine the chemical characteristics, antioxidant activity, total phenol, and caffeine contents in coffee of the Red Sayer variety date seeds. Coffee of date seeds is made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Caffeine content: The results in Table 3 indicated that no significant differences among different types of date seeds. However, significant differences were observed between Yemeni coffee beans and all types of date seeds, as caffeine was not detected in all date seeds, consistent with findings reported by [42,18 ] Conversely, Yemeni coffee beans showed increasing caffeine content, which can adversely affect human health by inducing cardiac muscle stress and being considered stimulants [14].The lower the caffeine content, the better for overall health. Several studies have indicated that continuous caffeine consumption lead to stress and anxiety [31] , headaches [17] ,…”
Section: Fiber Contentsupporting
confidence: 82%
“…Caffeine content: The results in Table 3 indicated that no significant differences among different types of date seeds. However, significant differences were observed between Yemeni coffee beans and all types of date seeds, as caffeine was not detected in all date seeds, consistent with findings reported by [42,18 ] Conversely, Yemeni coffee beans showed increasing caffeine content, which can adversely affect human health by inducing cardiac muscle stress and being considered stimulants [14].The lower the caffeine content, the better for overall health. Several studies have indicated that continuous caffeine consumption lead to stress and anxiety [31] , headaches [17] ,…”
Section: Fiber Contentsupporting
confidence: 82%
“…No traces of caffeine in the date seeds were found [2]. Further studies were performed, but caffeine could not be detected [10,32,34,35,44,60,63,64].…”
Section: Caffeinementioning
confidence: 95%
“…Among the different components of the date fruit, the seeds exhibit the highest antioxidant activity, with an IC 50 value of approximately 24 µg/mL. Date seed coffee, which has a very strong antioxidant activity [32], is linked to its high phenolic content [26,37]. Phenolic compounds preserve fruits against microbial and parasite infections, as well as photo-oxidation.…”
Section: Phenolic Acids and Flavonoidsmentioning
confidence: 99%